2015
DOI: 10.1002/hbm.22811
|View full text |Cite
|
Sign up to set email alerts
|

5‐HTTLPR differentially predicts brain network responses to emotional faces

Abstract: The effects of the 5-HTTLPR polymorphism on neural responses to emotionally salient faces have been studied extensively, focusing on amygdala reactivity and amygdala-prefrontal interactions. Despite compelling evidence that emotional face paradigms engage a distributed network of brain regions involved in emotion, cognitive and visual processing, less is known about 5-HTTLPR effects on broader network responses. To address this, we evaluated 5-HTTLPR differences in the whole-brain response to an emotional face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Previous behavior genetic studies on the relationship between the 5‐HTTLPR/rs25531 and FP, relying on single task paradigms had provided inconclusive results (Antypa et al ; Boll & Gamer ; Defrancesco et al ; Fisher et al ; Jonassen et al 2012a,b; Székely et al ). Therefore, the reported relationship between the 5‐HTTLPR/rs25531 genotype and the facial emotion and identity perception observed in the present study, when considering latent variables, is an important finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous behavior genetic studies on the relationship between the 5‐HTTLPR/rs25531 and FP, relying on single task paradigms had provided inconclusive results (Antypa et al ; Boll & Gamer ; Defrancesco et al ; Fisher et al ; Jonassen et al 2012a,b; Székely et al ). Therefore, the reported relationship between the 5‐HTTLPR/rs25531 genotype and the facial emotion and identity perception observed in the present study, when considering latent variables, is an important finding.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies on emotion recognition accuracy are inconsistent as well. Boll and Gamer () found a better general emotion recognition accuracy for the low as compared with the high expressing 5‐HTT group; other studies reported a better recognition accuracy in the low 5‐HTT group specifically for fear (Defrancesco et al ; Fisher et al ) or negative emotions in general (Antypa et al ); still others showed better recognition accuracy for sad and fearful faces in the high expressing 5‐HTT group (Jonassen et al 2012a,b; Székely et al ).…”
Section: Neural Underpinnings Of Face Cognitionmentioning
confidence: 97%
“…The latter have predominantly subtracted responses to non-threatening visual stimuli from responses towards either facial stimuli expressing aversive emotions or sets of more generally aversive scenes (Adolphs, 2008). A number of these tasks have been applied as probe tasks of amygdalar functioning in different patient groups (Broome et al, 2015), across individuals with different personality traits (Clauss et al, 2015; Kennis et al, 2013) and in studies of development and genetics (Fisher et al, 2015; Wu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Only 25 studies fulfilled the inclusion criteria for the purpose of the review. 22 reported brain activation differences associated with the 5-HTTLPR polymorphism (Battaglia et al, 2012;Bertolino et al, 2005;Canli et al, 2006Canli et al, , 2008Dannlowski et al, 2010;Domschke et al, 2012;Fisher et al, 2015Fisher et al, , 2014Hariri et al, 2005Hariri et al, , 2002Lee and Ham, 2008;Lonsdorf et al, 2011;O'Nions et al, 2011;Pezawas et al, 2005;Surguladze et al, 2012Surguladze et al, , 2008Thomason et al, 2010;Volman et al, 2013;Von dem Hagen et al, 2011;Walsh et al, 2012;Waring et al, 2014;Wiggins et al, 2014). Two of the 22 5-HTTLPR studies reported additionally TPH2 genotype related brain activation (Canli et al, 2008;Lee and Ham, 2008).…”
Section: Imaging Genetics Studies Of 5-httlpr Effects On Facial Affecmentioning
confidence: 99%
“…Unlike Lee and Ham who reported effects related to the single genes (Lee and Ham, 2008), Canli and colleagues reported an additive gene-gene effect of TPH2 with 5-HTTLPR alleles (Canli et al, 2008). Of the 25 studies, only eleven groups focused on the SNP rs25531 in their analyses, a functional polymorphism suggested to modulate the transcriptional efficacy of 5-HTTLPR (Canli et al, 2006;Costafreda et al, 2013;Dannlowski et al, 2010Dannlowski et al, , 2008Domschke et al, 2012;Fisher et al, 2015Fisher et al, , 2014O'Nions et al, 2011;Surguladze et al, 2012;Thomason et al, 2010;Wiggins et al, 2014). Two groups decided to follow a biallelic approach due to group size issues (Canli et al, 2006;Thomason et al, 2010).…”
Section: Imaging Genetics Studies Of 5-httlpr Effects On Facial Affecmentioning
confidence: 99%